PENGARUH KELELAHAN KERJA TERHADAP KINERJA DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING PADA PEKERJA ROTTE BAKERY BAGIAN PRODUKSI - Dwifa Dwifa Nadira; Daulay Nauli Iwan; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of work fatigue on performance with workstress as an intervening variable in the production division of Rotte Bakery workers. Thepopulation in this study included all workers in the production division of Rotte Bakery,amounting to 68 people. Primary data were collected using a questionnaire as aninstrument to prove the results of the study, to test the hypothesis in this study using PathAnalysis (path analysis) with the help of the SPSS (Statistical Package of Social Science)program. The sampling technique chosen for this study is a non-probability samplingtechnique using the saturated sampling method (census sampling), namely the entireRotteam production section of Rotte Bakery, totaling 68 people. The results showed that:1) work fatigue had a negative and significant effect on the performance variables ofRotte Bakery workers in the production section, 2) job fatigue had a positive andsignificant effect on work stress variables for Rotte Bakery workers in the productionsection, 3) work stress had a negative and no effect. significant to the performancevariable, 4) work stress has no effect as an intervening variable or a variable thatmediates the relationship between work fatigue and performance. Keywords: Work Fatigue, Job Stress, Performance